Penerapan Alat Pengiris Gadung Berbasis Teknologi Tepat Guna untuk Mendukung Produktivitas UMKM - Putra, Dhanang Eka; Retnowati, Naning; Djamali, R. Abdoel; Marseva, Amalia Dwi; Cahyaningrum, Deltaningtyas Tri; Andini, Paramita; Mualimin, Lulus (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Gadung is a type of tuber that can be consumed after undergoing a process to remove its toxins. UD. Gadung Badean is an MSME that produces gadung chips. The process of slicing gadung tuber at UD. Gadung Badean is still carried out traditionally with a manual slicer, which requires a long time and greater resources. This community service activity aims to introduce and implement an efficient and easy-to-use appropriate technology in the form of a gadung slicer. The activity was carried out through socialization and training. Results showed that the use of the gadung slicer can increase the speed of the production process and potentially increase production capacity.